TRACER STUDY ALUMNI MAGISTER MANAJEMEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS MATARAM, 2020 - Akhmad Saufi; Hermanto Hermanto; Muttaqillah Muttaqillah (Master of Management, Mataram University, 2021)
Tracer studies help educational institutions obtain information to increase the relevance of their curriculum to meet employment’s need and improve the graduate performance. This applied research aims to evaluate the implementation of study programs in order to increase the relevance of the curriculum and the graduate performances. This research adopts a qualitative approach. 77 informants were involved in the research, consisting of 64 alumni and 13 stakeholders. Data were collected through online interviews and questionnaires containing open-ended questions, and then analyzed using content analysis. The results showed that the implementation of study programs, service quality, curriculum relevance, and alumni performance were rated at